Descent toward the Icehouse: Eocene sea surface cooling inferred from GDGT distributions. (27th July 2015) - Inglis, Gordon N.; Farnsworth, Alexander; Lunt, Daniel; Foster, Gavin L.; Hollis, Christopher J.; Pagani, Mark; Jardine, Phillip E.; Pearson, Paul N.; Markwick, Paul; Galsworthy, Amanda M. J.; Raynham, Lauren; Taylor, Kyle. W. R.; et al.
Abstract The TEX86 proxy, based on the distribution of marine isoprenoidal glycerol dialkyl glycerol tetraether lipids (GDGTs), is increasingly used to reconstruct sea surface temperature (SST) during the Eocene epoch (56.0–33.9 Ma). Here we compile published TEX86 records, critically reevaluate them in light of new understandings in TEX86 palaeothermometry, and supplement them with new data in order to evaluate long‐term temperature trends in the Eocene. We investigate the effect of archaea other than marine Thaumarchaeota upon TEX86 values using the branched‐to‐isoprenoid tetraether index (BIT), the abundance of GDGT‐0 relative to crenarchaeol (%GDGT‐0), and the Methane Index (MI). We also introduce a new ratio, %GDGTRS, which may help identify Red Sea‐type GDGT distributions in the geological record. Using the offset between TEX86H and TEX86L (ΔH‐L) and the ratio between GDGT‐2 and GDGT‐3 ([2]/[3]), we evaluate different TEX86 calibrations and present the first integrated SST compilation for the Eocene (55 to 34 Ma). Although the available data are still sparse some geographic trends can now be resolved. In the high latitudes (>55°), there was substantial cooling during the Eocene (~6°C). Our compiled record also indicates tropical cooling of ~2.5°C during the same interval. Using an ensemble of climate model simulations that span the Eocene, our results indicate that only a small percentage (~10%) of the reconstructed temperature change can be ascribed to ocean gateway reorganization or paleogeographic change. Collectively, this indicates that atmospheric carbon dioxide (pCO2) was the likely driver of surface water cooling during the descent toward the icehouse.